Early Maternal Depression and Social Skills in Adolescence: A Marginal Structural Modeling Approach. Issue 4 (10th February 2014) - DeRose, Laura M.; Shiyko, Mariya; Levey, Simone; Helm, Jonathan; Hastings, Paul D.
Abstract Early maternal depression is a risk factor that may have adverse effects on adolescent social skills. Although evidence indicates links between early maternal depression and social outcomes during early childhood, whether an association extends to adolescence needs further examination. We tested the possible long‐term association between early maternal depression and adolescent social skills using a national secondary dataset. A secondary objective was to test if maternal parenting at the transition to adolescence mediated the association, with the notion that adverse outcomes of early maternal depression could be ameliorated by positive parenting practices at an important developmental transition. Data were obtained from the National Institute of Child Health and Human Development Study of Early Child Care and Youth Development. Marginal structural modeling within the context of structural equation modeling revealed a significant association between early maternal depression and adolescent social skills while controlling for maternal depression during pre‐adolescence and adolescence. Maternal parenting skills partially mediated the association between early maternal depression and mother report of adolescent social skills. These findings have important implications for understanding the link between early maternal depression and adolescent social skills, and for informing parenting practices during pre‐adolescence.